Gestational weight gain and pregnancy outcomes: Findings from North Indian pregnancy cohort - Ranadip Chowdhury; Nitika ▪; Tarun Shankar Choudhary; Neeta Dhabhai; Pratima Mittal; Rupali Dewan; Jasmine Kaur; Ritu Chaudhary; Anuradha Tamaria; Rajiv Bahl; Sunita Taneja; Nita Bhandari (Wiley, 2022)
Abstract Despite the high prevalence of inadequate gestational weight gain (GWG) and adverse pregnancy outcomes, very few studies have addressed the association between GWG and pregnancy outcomes in South Asia. Our objectives were to estimate the prevalence of GWG during the second and third trimesters within, below and above the Institute of Medicine (IOM) guidelines, and to estimate the effect of the rate and adequacy of GWG on gestational age at the time of delivery, weight, length, length‐for‐age z‐score (LAZ), weight‐for‐length z‐score (WLZ) and adverse pregnancy outcomes, namely prematurity, small‐for‐gestational age (SGA), low birth weight (LBW), stunting and wasting at birth. We analysed data from the intervention group of the Women and Infants Integrated Interventions for Growth Study (WINGS), which is an ongoing individually randomized factorial design study. Of the 1332 women analysed, 40.2% [95% confidence interval (CI) 37.5 to 42.8] had GWG below the IOM guidelines. For every 100‐g/week increase in GWG, birth weight increased by 61 g, birth length by 0.16 cm, LAZ score by 0.08 SD, WLZ score by 0.14 SD, and gestational age at birth by 0.48 days. Women with GWG below the IOM guidelines had a higher relative risk of adverse pregnancy outcomes (44% for LBW, 27% for SGA, 32% for stunting and 42% for wasting at birth) than women who had GWG within the IOM guidelines, except for prematurity. The association between GWG and LAZ scores at birth was modified by early pregnancy body mass index (BMI). GWG is a strong predictor of newborn anthropometric outcomes and duration of gestation but not prematurity.